Komunikasi Krisis Dana Indonesia Pada Kasus “Saldo Hilang” Untuk Mempertahankan Reputasi Perusahaan - Diarra , Adinda Ratiza; Rahman, Siena Gita (PT Literasi Nusantara Publisher, 2024)
In the era of economic digitalization 4.0, the e-wallet phenomenon is emerging and growing rapidly. In mid-2018 DANA as a digital wallet was officially launched. This year there are more and more DANA users. However, a big case occurred in the digital wallet application, namely